Revision of the Afrotropical genus Protoleptops Heinrich, 1967 (Hymenoptera, Ichneumonidae, Ichneumoninae), with description of a new species from Burundi - Dal Pos, Davide; De Ketelaere, Augustijn; Di Giovanni, Filippo (Pensoft Publishers, 2024)
This study presents a comprehensive revision of the genus Protoleptops Heinrich, 1967. We describe a new species, P. nyeupe Dal Pos & Di Giovanni, sp. nov. , from Burundi, marking the first documented occurrence of an Ichneumoninae species in the country. Additionally, we provide the first diagnostic description of the female P. farquharsoni Heinrich, 1967 and report a new occurrence of this species in KwaZulu-Natal. Furthermore, we document P. magnificus for Mpumalanga (South Africa) and P. angolae Heinrich, 1967 in Uganda, thereby extending the known range of the latter into East Africa. A detailed catalogue of all species within the genus Protoleptops is also included.